The Effect of Work Discipline and Rewarding on Employee Performance at PT. Pesona Inti Rasa - Fauzia Mei Salsabillah; Amin Hou; Debora Tambunan; Emma Novirsari; Sabaruddin Chaniago (CV. Aksara Global Akademia, 2023)
The organization has human resources, which is an essential factor as a driving force for the continuity of an organization; an organization can progress and develop if it has quality and reliable resources; as a measuring tool, it can be seen from employee performance where employee work can be used as an assessment of quality employees or not, then it can also be seen from employee performance whether employees are professional in their work or not. This type of research is quantitative research. The research population is permanent PT Pesona Inti Rasa employees, totaling 80 employees; the sampling technique used is a saturated sample. The study's results stated that work discipline does not affect employee performance; giving rewards affects employee performance.